GEOCHEMISTRY OF VOLCANIC ROCKS FROM TRANSFORM MARGINS: EVIDENCE FROM THE ALCHAN BASIN, NORTHWESTERN PRIMORIE - Simanenko V.P.; Golozubov V.V.; Sakhno V.G. (My University, 2006)
Geological, petrochemical, and geochemical data are reported for volcanic rocks of a Cretaceous pull-apart basin in the Tan Lu strike-slip system, Asian continental margin. A comparison of these volcanic rocks with magmatic rocks from typical Cenozoic transform margins in western North America and rift zones of Korea made it possible to distinguish some indicator features of transform-margin volcanic rocks. Magmatic rocks from strike-slip extension zones bear island-arc, within-plate, and, occasionally, depleted MORB geochemical signatures. In addition to calc-alkaline rocks, there are bimodal volcanic series. The rocks are characterized by high K2O, MgO, and TiO2 contents. They show variable enrichment in LILE relative to HFSE, which is typical of island-arc magmas. At the same time, they are rich in compatible transition elements, which is a characteristic of within-plate magmas. The trace-element distribution patterns normalized to MORB or primitive mantle usually display a negative Ta-Nb anomaly typical of suprasubduction settings. Their Ta/Nb ratio is lower, whereas Ba/Nb, Ba/La, and La/Yb are higher than those of some MORB and OIB. In terms of trace-element systematics, for example, Ta-Th-Hf, Ba/La-(Ba/La)n, (La/Sm)n-La/Hf, and others, they fall within the area of mixing of magmas from several sources (island arc, within plate, and depleted reservoirs). The magmatic rocks of transform settings display a sigmoidal chondrite-normalized REE distribution pattern, with a negative slope of LREE, depletion in MREE, and an enriched or flat HREE pattern. The magmas with mixed geochemical characteristics presumably originated in a transform margin setting in local extension zones under the influence of mantle diapirs, which caused metasomatism and melting of the lithosphere at different levels, and mixing of melts from different sources in variable proportions. © Pleiades Publishing, Inc. 2006.
Keywords: Alchan basin; Primorie; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая